Scientific Exegesis of Surah An-Nur, Verse 40: Analyzing the Maritime Metaphor - Naween, Wajeeha (Islamic Religious Education Departement, 2026)
This study examines the maritime metaphor in Surah An-Nur, Verse 40, through a comparative analysis of classical tafsīr and modern scientific exegesis. The objective is to analyze how traditional spiritual interpretations of this verse correspond with contemporary oceanographic discoveries. The research employs a qualitative descriptive-analytical method with content analysis, systematically comparing classical exegetical works (al-Ṭabarī, Ibn Abī Ḥātim, Muqātil bin Sulaymān, Yaḥyā bin Salām) with peer-reviewed marine science literature. The findings reveal that the verse operates effectively on two complementary levels: first, as a profound theological parable illustrating spiritual blindness according to classical commentators; and second, as an empirically accurate description corresponding to modern marine science discoveries, specifically, the exponential absorption of light spectra creating layered darkness in the aphotic zone (below 1,000 meters), and the phenomenon of internal waves traveling along density gradients. This dual coherence contributes to the discourse on I'jāz al-'Ilmī (Scientific Inimitability) by demonstrating how the Qur'anic description corresponds to oceanic phenomena that were historically unknowable to seventh-century observers. The study concludes that modern scientific interpretation enriches rather than replaces the classical spiritual meaning, establishing a hermeneutical bridge that maintains theological integrity while engaging contemporary scientific understanding.